Properties of laminated veneer lumber from oil palm trunk veneer using different adhesives / Muhammad Najib Yusoff, Siti Noorbaini Sarmin and Ahmad Sardey Idris - Yusoff, Muhammad Najib; Sarmin, Siti Noorbaini; Idris, Ahmad Sardey (2011)
This study was undertaken is to determine the properties of laminated veneer lumber from oil palm trunk by using different adhesive and spread level. Experimental LVL panel from OPT veneers bonded with Polyvinyl acetate (PVAc) and Phenol Formaldehyde (PF) were produced with two adhesive spread levels; 180g/m2 and 360g/m2 for single glue line. Density, bending strength and tensile shear strength were then accessed based on BS 65666: Part 8:1985 standard. From the study it showed that, tensile shear strength was higher in panel bonded with PF with PVAC. The panels glued with PF using 360g/m2 spread level showed better in MOR and MOE compare with other. Density of panel manufactured using PF using 180g/m2 was higher compare with panel bonded with PF using 360g/m2 and PVAc using 180 and 360g/m2 spread level.